2021
DOI: 10.3389/fphar.2021.808735
|View full text |Cite
|
Sign up to set email alerts
|

The Hexosamine Biosynthetic Pathway Links Innate Inflammation With Epithelial-Mesenchymal Plasticity in Airway Remodeling

Abstract: Disruption of the lower airway epithelial barrier plays a major role in the initiation and progression of chronic lung disease. Here, repetitive environmental insults produced by viral and allergens triggers metabolic adaptations, epithelial-mesenchymal plasticity (EMP) and airway remodeling. Epithelial plasticity disrupts epithelial barrier function, stimulates release of fibroblastic growth factors, and remodels the extracellular matrix (ECM). This review will focus on recent work demonstrating how the hexos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…Finally, UDP-N-acetylhexosamine pyrophorylase (UAP) synthesizes UDP-GlcNAc and diphosphate from N-acetylglucosamine-1-phosphate and uridine triphosphate (UTP). Crucial enzymes within the HBP pathway such as (GFAT1, GNA1, PGM3) are elevated in a process shared by various ILDs, namely when epithelial-mesenchymal plasticity (EMP) is induced by TGF-β ( 100 ). This elevation is necessary for the N-glycosylation process and subsequent secretion of extracellular matrix (ECM) components, which is vital for airway remodeling, highlighting fibrosis-promoting role of the HBP pathway.…”
Section: Protein Glycosylation Is Linked To Metabolismmentioning
confidence: 99%
“…Finally, UDP-N-acetylhexosamine pyrophorylase (UAP) synthesizes UDP-GlcNAc and diphosphate from N-acetylglucosamine-1-phosphate and uridine triphosphate (UTP). Crucial enzymes within the HBP pathway such as (GFAT1, GNA1, PGM3) are elevated in a process shared by various ILDs, namely when epithelial-mesenchymal plasticity (EMP) is induced by TGF-β ( 100 ). This elevation is necessary for the N-glycosylation process and subsequent secretion of extracellular matrix (ECM) components, which is vital for airway remodeling, highlighting fibrosis-promoting role of the HBP pathway.…”
Section: Protein Glycosylation Is Linked To Metabolismmentioning
confidence: 99%
“…The studies conducted in order to evaluate a possible connection between epigenetics, EMP, and fibrosis are leading to the first discoveries, for example, in airway persistent inflammation [ 95 ], but require further investigation. On the contrary, the field of studies conducted on the role of epigenetic modifications in EMT-dependent fibrosis is much more flourishing.…”
Section: Epigenetics Regulation Of Emp/emt-dependent Fibrosismentioning
confidence: 99%
“…These entities activate pattern recognition receptors (PRRs) retinoic acid inducible gene-I (RIGI) and Toll-like receptor 3 (TLR3) ( 15 17 ) that form active TANK-Binding Kinase and IκB Kinase (IKK) signalsomes, stimulating interferon regulatory factor (IRF1), activating protein 1 (AP1) and NF-κB ( 17 19 ). More recent work has shown that RSV is also a potent activator of the unfolded protein response that results in inducible phenotypic changes known as “epithelial plasticity” and upregulation of N-glycosylation pathways controlling extracellular matrix production and mucin secretion ( 20 , 21 ). The exuberant, innate response of small airways epithelium explains the observations that, in fatal cases of RSV LRTI, acute hypoxic respiratory failure is associated with mucus plugging and ventilation-perfusion mismatch in the small airways ( 11 ).…”
Section: Introductionmentioning
confidence: 99%